Evaluation of Silica-H2SO4 as an Efficient Heterogeneous Catalyst for the Synthesis of Chalcones - Nazamid Saari; Khalid Mohammed Khan; Aeysha Sultan; Abdul Rauf Raza; Muhammad Nawaz Tahir; Muhammad Abbas (Molecules, 2013)
We report an efficient silica-H2SO4 mediated synthesis of a variety of chalcones that afforded the targeted compounds in very good yield compared to base catalyzed solvent free conditions as well as acid or base catalyzed refluxing conditions.